2008
DOI: 10.1007/s00262-008-0591-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of arginase I activity and expression by both PD-1 and CTLA-4 on the myeloid-derived suppressor cells

Abstract: An elevated number of Gr-1(+)CD11b(+) myeloid-derived suppression cells (MDSCs) has been described in mice and human bearing tumor and associated with immune suppression. Arginase I production by MDSCs in the tumor environment may be a central mechanism for immunosuppression and tumor evasion. In this study and before, we found that Gr-1(+)CD11b(+) MDSCs from ascites and spleen of mice bearing ovarian 18D carcinoma express a high level of PD-1, CTLA-4, B7-H1 and CD80 while other co-stimulatory molecules, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 36 publications
7
69
1
Order By: Relevance
“…Although it was anticipated that this population would comprise immunosuppressive MDSCs, our results were not consistent with previous studies (20)(21)(22). This population did not represent vascular leukocyte cells based on either phenotypic or functional differences (23)(24)(25).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Although it was anticipated that this population would comprise immunosuppressive MDSCs, our results were not consistent with previous studies (20)(21)(22). This population did not represent vascular leukocyte cells based on either phenotypic or functional differences (23)(24)(25).…”
contrasting
confidence: 56%
“…We initially assumed that the CD11b + Gr-1 + cells accumulating in the spleen (ID8/spleen) and ascites (ID8/ascites) of the ID8-bearing mice would consist of MDSCs as previously described (20,21,29). Surprisingly, CD11b + Gr-1 + cells from both compartments did not suppress but rather enhanced both CD4 + and CD8 + T cell proliferation in vitro in both a nonspecific and an Ag-FIGURE 1.…”
Section: Cd11b + Gr-1 + Cells From Malignant Ascites Are Not Mdscsmentioning
confidence: 99%
“…[2][3][4] PD-1 is a transmembrane protein that belongs to the CD28 family of the immunoglobulin superfamily and, within hematological populations, is expressed on T and B lymphocytes, NK and myeloid cells. [5][6][7][8] Expression of PD-1 is induced on T cells shortly after TCR stimulation, and increased numbers of tumor infiltrating PD-1 C lymphocytes have been associated with prolonged survival of patients with metastatic melanoma. 9 However, ligation of PD-1 can induce programmed cell death in lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, CD80 expression is upregulated on tumorderived MDSCs, [42][43][44][45] as well as on spleen-derived MDSCs in some tumor models. 24,42 The use of CD80-specific neutralizing antibodies or small interfering ribonucleic acid (siRNA) against CD80 was shown to partially inhibit the suppressive function of MDSCs, indicating that CD80 does play a role in the suppressive function of MDSCs but that other factors are also involved.…”
Section: Ly6gmentioning
confidence: 81%
“…41 In different tumor models it has been shown that CD80 expression is upregulated on tumor-derived MDSCs. [42][43][44][45] Moreover in some tumor models CD80 expression was also elevated on spleen-derived MDSCs. 24,42 These conflicting observations could be explained by the use of different tumor models (subcutaneously implanted tumors vs. tumors grown as ascites), the disease stage at which CD80 expression was evaluated and the subset of MDSCs under investigation.…”
Section: Murine Mdscsmentioning
confidence: 99%